Analysis of Gender Representation in "My Next Words": Unpacking First Grade Elementary School Students' Book - Vionisa, Evatul; Zahro, Syifa Khuriyatuz (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study addresses the pervasive issue of gender representation in educational materials, focusing on the elementary school context. The research problem centers on assessing how gender is portrayed in the textbook titled "My Next Words for Elementary School," designed for 1st-grade students. The purpose of the research is to provide a comprehensive analysis of the textbook's content, examining categories such as omission, firstness, occupational visibility, nouns, masculine generic construction, and adjectives, within the framework proposed by Porreca (1984). The methodology employed is a content analysis with a descriptive qualitative design. The study meticulously examines the 13 chapters of the textbook, analyzing both textual and illustrative elements. The findings reveal a balanced gender representation in text and illustrations, fostering an inclusive learning environment. The arrangement of sentences demonstrates an equitable introduction of male and female characters, promoting a sense of equality. The textbook breaks away from traditional gender norms by incorporating diverse occupational roles, ensuring both male and female characters engage in various professions. Nouns related to gender are thoughtfully selected to avoid reinforcing stereotypes, and masculine generic construction is balanced. Adjectives are distributed fairly between male and female characters. In the findings, the study emphasizes the contribution of the analyzed textbook in promoting gender inclusivity and avoiding stereotypes in elementary education. This research has implications for curriculum development and instructional material design, advocating for more inclusive and gender-sensitive educational resources in elementary schools.